Discourse on the Separation of the National Police from the Ministry of Constitutional Law and Constitutional Politics - Wijoyo, Hadi; Suharto, Suharto; Virdaus, Saivol (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
The position of the National Police of the Republic of Indonesia (Polri), which is under the President and has structural and functional links with certain ministries, raises debates about the level of its independence, especially in the implementation of law enforcement functions that demand neutrality and freedom from political intervention. This study aims to analyze the constitutional basis and institutional implications of the relationship between the National Police and ministries in the Indonesian constitutional system. The method used is normative legal research with a statutory and conceptual approach, which focuses on the study of legal norms and principles that govern the position and institutional relations of the National Police. The results of the analysis show that the arrangement of the relationship between the National Police and the ministry still leaves ambiguity in the institutional design, which has the potential to affect the independence of law enforcement. Therefore, the discourse on the separation of the National Police from the ministries has a strong normative basis, both in the perspective of constitutional law and in the framework of security sector reform. The main contribution of this research lies in strengthening normative arguments regarding the importance of restructuring the institutional relationship of the National Police in order to clarify its constitutional position, increase independence in law enforcement, and maintain consistency with the principles of a democratic state of law.